On Intersectionality: How Complex Patterns of Discrimination Can Emerge From Simple Stereotypes. (August 2020) - Hester, Neil; Payne, Keith; Brown-Iannuzzi, Jazmin; Gray, Kurt
Patterns of discrimination are often complex (i.e., multiplicative), with different identities combining to yield especially potent discrimination. For example, Black men are disproportionately stopped by police to a degree that cannot be explained by the simple (i.e., additive) effects of being Black and being male. Researchers often posit corresponding mental representations (e.g., intersectional stereotypes for Black men) to account for these complex outcomes. We suggest that complex discrimination can be explained by simple stereotypes combined with threshold models of behavior—for example, "if someone's threat level seems higher than X, stop that person." Simulations provide proof of this concept. We show how gender-by-race discrimination in both promotions and police stops can be explained by simple stereotypes. We also explore race-by-age discrimination in police stops, in which racial disparities are greater for young adolescents. This work suggests that complex behaviors can sometimes arise from relatively simple cognitions.